Evaluation and Management of First-Time Seizure in Adults - Abdennadher, Myriam; Saxena, Aneeta; Pavlova, Milena K. (Seminars in Neurology, 2021)
First seizures are often perceived as devastating events by patients and their families due to the fear of having a life-long disease. One in 10 people experiences one or more seizures during their lifetime, while 1 in 26 people develops epilepsy. Acute symptomatic seizures are often related to a provoking factor or an acute brain insult and typically do not recur. Careful history and clinical examination should guide clinicians' management plans. Electroencephalography and brain imaging, preferably with epilepsy-specific magnetic resonance imaging, may help characterize both etiology and risk of seizure recurrence. Antiepileptic drugs should be initiated in patients with newly diagnosed epilepsy. In patients without an epilepsy diagnosis, the decision to prescribe drugs depends on individual risk factors for seizure recurrence and possible complications from seizures, which should be discussed with the patient. Counseling about driving and lifestyle modifications should be provided early, often at the first seizure encounter.
Keywords: first seizure evaluation; antiepileptic drug; electroencephalography; epilepsy